MATHEMATICAL CRITICAL THINKING SKILLS OFSEVENTH-GRADE STUDENTS IN SOLVING FRACTION PROBLEMS - Sugianto, Sugianto (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematical critical thinking skills (MCTS) constitute an essential competence in mathematics learning, as they assist students in understanding concepts, analyzing problems, and drawing logical conclusions. However, various studies indicate that students’ mathematical critical thinking skills remain at a suboptimal level, particularly in the topic of fractions, which serves as a foundational concept for understanding more advanced mathematical ideas. This study aims to describe the mathematical critical thinking skills of seventh-grade students at MTs Al-Irsyad Riau in learning fractions based on the indicators of interpretation, analysis, evaluation, and inference. This research employed a descriptive method with a quantitative approach supported by qualitative analysis of students’ responses. The participants consisted of 33 seventh-grade students. Data were collected through an essay test comprising four questions designed based on indicators of mathematical critical thinking skills. The findings revealed that students’ mathematical critical thinking skills were at a moderate level, with an achievement percentage of 49.24%. Analysis based on the indicators showed that the skills of interpretation, analysis, evaluation, and inference were all within the moderate category, with the highest achievement found in the inference indicator. These findings indicate that students possess basic critical thinking abilities; however, their application in solving mathematical problems still requires further strengthening. Therefore, mathematics instruction needs to be designed to encourage reasoning activities, problem solving, and mathematical discussion in order to develop students’ critical thinking skills more optimally. Keterampilan berpikir kritis matematis (KBKM) merupakan salah satu kemampuan penting dalam pembelajaran matematika karena berperan dalam membantu siswa memahami konsep, menganalisis permasalahan, serta menarik kesimpulan secara logis. Namun, berbagai penelitian menunjukkan bahwa kemampuan berpikir kritis matematis siswa masih berada pada tingkat yang belum optimal, khususnya pada materi pecahan yang menjadi dasar bagi pemahaman konsep matematika lanjutan. Penelitian ini bertujuan untuk mendeskripsikan keterampilan berpikir kritis matematis siswa kelas VII MTs Al-Irsyad Riau pada materi pecahan berdasarkan indikator interpretasi, analisis, evaluasi, dan inferensi. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif yang didukung analisis kualitatif terhadap jawaban siswa. Subjek penelitian berjumlah 33 siswa kelas VII. Data dikumpulkan melalui tes uraian yang terdiri dari empat soal yang dirancang berdasarkan indikator keterampilan berpikir kritis matematis. Hasil penelitian menunjukkan bahwa KBKM siswa berada pada kategori cukup dengan persentase capaian sebesar 49,24%. Analisis berdasarkan indikator menunjukkan bahwa kemampuan interpretasi, analisis, evaluasi, dan inferensi seluruhnya berada pada kategori cukup, dengan capaian tertinggi pada indikator inferensi. Temuan ini menunjukkan bahwa siswa telah memiliki kemampuan dasar dalam berpikir kritis, namun penerapannya dalam menyelesaikan permasalahan matematis masih memerlukan penguatan. Oleh karena itu, pembelajaran matematika perlu dirancang untuk mendorong aktivitas penalaran, pemecahan masalah, serta diskusi matematis guna mengembangkan keterampilan berpikir kritis siswa secara lebih optimal.